Pengaruh Pemberian Jus Tomat Terhadap Penurunan Tekanan Darah pada Pasien Hipertensi: Tinjauan Literatur - Gita Cahyani; Siti Rohimah; Yoga Ginanjar (Jurnal Keperawatan Galuh, 2025)
The prevalence of hypertension in Indonesia continues to increase, characterized by increased blood pressure due to vasoconstriction of blood vessels. Hypertension management can be carried out through non-pharmacological approaches, including complementary therapies such as tomato juice. This study aims to identify and analyze research articles on the effect of tomato juice on lowering blood pressure in hypertensive patients. The study design used a literature review. Article searches were conducted through Google Scholar, ScienceDirect, and PubMed databases, with a search period of 2015–2025. A total of 12 articles that met the inclusion criteria were analyzed. The review results showed that administering tomato juice at a dose of 150–250 grams per day for 1-4 weeks contributed to a reduction in systolic and diastolic blood pressure in the range of 1-10 mmHg. This effect is related to the content of lycopene, bioflavonoids, and potassium, which have antioxidant and vasodilatory activities. Although the majority of studies showed benefits, variations in design, intervention duration, and sample characteristics between studies indicate the need for cautious interpretation of the results and the need for research with more robust methodology. In conclusion, tomato juice has potential as a supportive non-pharmacological intervention to lower blood pressure in hypertensive patients. However, these findings require further study through more standardized experimental studies before being widely integrated into primary healthcare practice.